Nanotechnology associated with Grape seed Extract and Applications - Montagner, Giane Engel; Fogaça, Aline de Oliveira; Gomes, Patricia (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
The aim of this study was to investigate the main nanostructures used to protect polyphenols present in grape seed extract and their actions. This study is an integrative review of the literature. The data collection was performed on 31st may, 2019, in the electronic databases Web of Science and Bireme (Virtual Health Library). The Boolean descriptors and operators used were: Nano* AND Grape seed AND Extract. English, Spanish or Portuguese were included in the sample. The search in the databases resulted in the collection of 132 articles, of which 12 fulfilled the inclusion criteria. As all the nanoparticles containing grape seed extract maintained or increased the activity of the polyphenols present in the extract, thus showing that the use of nanotechnology is effective in protecting these bioactive compounds and can be used in health and food industry.